Agent by her side - Mello, Deborah Fletcher (Colton 911: Grand Rapids., 2020)
"If PI Kiely Colton must work with FBI agent Cooper Winston, she will. But to solve a cold case, she won't change her break-the-rules style to accommodate the single father's by-the-book principles. As the investigation progresses, Kiely finds herself inexplicably attracted to her exacting partner and enchanted by his adorable son. Will a ruthless killer put an end to their possible future before it really begins?"--